The Influence of Organizational Structure on Employee Work Effectiveness at the Medan Area District Office, Medan City - Dalimunte, Nurul; Rambe, Saima; Dewi, Ratna Sari (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to determine how much influence the Organizational Structure has on the Work Effectiveness of Employees at the Medan Atea District Office, Medan City. This study consists of the Independent Variable (X) Organizational Structure and Variable (Y) Employee Work Effectiveness. The sample of this study was all employees (PNS) at the Medan Area District Office, Medan City, totaling 30 employees. The method used in this study is a quantitative method. Data collection techniques in this study are interviews, questionnaires, and observations. Data analysis techniques use product moment correlation and significance tests. To determine the level of significance of the Influence of Organizational Structure on the Work Effectiveness of Employees at the Medan Area District Office, Medan City, a hypothesis test was conducted on r by determining the level of significance α = 5%. Determining the r table test n = 30. It is known based on data processing that the results of the r table product moment value with n = 48 and a 95% confidence level or 5% error is 0.361. Thus, r count 0.607 > r table 0.361. This means that there is a large influence between Organizational Structure on Employee Work Effectiveness. Thus, the proposed hypothesis can be accepted, namely that the magnitude of the influence of organizational structure can increase employee work effectiveness at the Medan Area District Office, Medan City.